Childhood Obesity and Maternal Personality Traits: A New Point of View on Obesity Behavioural Aspects - Francesco Precenzano; Daniela Smirni; Luigi Vetri; Pierluigi Marzuillo; Valentina Lanzara; Ilaria Bitetti; Margherita Siciliano; Emanuele Miraglia del Giudice; Maria Esposito; Nicola Santoro; Marco Carotenuto (MDPI AG, 2021)
The epidemic spread of childhood obesity in Western society has interested many researchers, who agree in defining it as a multifactorial disease in which not only eating habits and sedentary lifestyle play a role, but also genetic predisposition. The aim of this study was to analyze the personality profile of a group of mothers of children with obesity and to compare this profile to that of a group of mothers of children without obesity. A total of 258 mothers participated in the study (126 mothers of children with obesity and 132 mothers of children without obesity). Weight and height were measured and the body mass index was calculated. The Minnesota Multiphasic Personality Inventory second edition (MMPI-2), evaluating personality and psychological disorders, was used to evaluate the personality profile. The results suggested that mothers of children with obesity score higher than the mothers of children without obesity in all MMPI-2 subscales. In most of these subscales, the differences between the two groups of mothers were statistically significant and with a medium to high effect size. These data suggest a new perspective on childhood obesity, identifying it as a multifactorial pathology that requires a multimodal and multidisciplinary approach that also takes care of caregivers to ensure optimal therapeutic efficacy.